A Misleading Angioedema: Case Report - Vale, Gonçalo (2022)
Hereditary angioedema is a rare clinical syndrome characterized by episodic nonpitting swelling of the subcutaneous and submucosal tissues due to a deficiency or lack of function of the C1 esterase inhibitor. It commonly affects nondependent areas, such as the tongue, lips, face, and upper airways. Potentially a life-threatening disease, it mostly resolves without complications. It is often unrecognized or misdiagnosed after the first episode. There are a number of triggers for hereditary angioedema, including medications, namely angiotensin-converting enzyme inhibitors. Their use is increasing in the pediatric age due to the higher prevalence of obesity and its comorbidities. Angioedema is a possible known side effect. We present a case report of a female teenager under angiotensin-converting enzyme inhibitor therapy who developed recurrent angioedema. The use of an angiotensin-converting enzyme inhibitor was a confounding factor for the diagnosis of hereditary angioedema.